The Controversial Role of IL-33 in Lung Cancer - Yang, Keshan; Tian, Cheng; Zhang, Chengliang; Xiang, Ming (Frontiers in Immunology, 2022)
Interleukin-33 (IL-33) belongs to the interleukin-1 (IL-1) family, and its structure is similar to interleukin-18. When cells are damaged or undergo necrosis, mature form of IL-33 is secreted as a cytokine, which can activate the immune system and provide danger signals. The IL-33/ST2 signaling pathway is composed of IL-33, suppression of tumorigenicity 2 (ST2), and IL-1 receptor accessory protein (IL-1RAcP). IL-33 has been reported to be strongly associated with lung cancer progression, and can exhibit opposite effects on lung cancer under different conditions. In this review, we have summarized the structure and basic functions of IL-33, its possible function in immune regulation, and its role in pulmonary fibrosis as well as in lung cancer. We have shed novel light on the dual regulation of IL-33 in lung cancer and proposed potential lung cancer treatment regimens, especially new immunotherapies, based on its mechanism of action.